Cognitive outcomes in adults with HIV-associated Tuberculous Meningitis - Albertyn, Christine Herculine (Department of Medicine, 2019)
Tuberculous meningitis (TBM) is a common cause of meningitis in adults in South Africa (1-3), second only to cryptococcal meningitis in studies of microbiologically confirmed meningitis, and accounting for 28% of cases in one (1). Conventional diagnostic tests for TBM are, however, relatively insensitive, and the true incidence is likely to be underreported. When both microbiological and clinical diagnostic criteria (4) are used in the same setting, the incidence of TBM rose to 57% (3), emerging as the most common cause of meningitis in adults in a district level hospital in the Western Cape. In the setting of high human immunodeficiency virus (HIV) and tuberculosis (TB) prevalence, approximately 88% of patients with definite or probable TBM are co-infected with HIV (3, 5) and six-month mortality in this group approaches 50% (3). Survivors may be left with long-term disability secondary to hydrocephalus, cranial neuropathies, seizures and strokes (6).